2017
DOI: 10.1177/0886260517747605
|View full text |Cite
|
Sign up to set email alerts
|

Perspective-Taking and Empathy Mitigate Family-of-Origin Risk for Electronic Aggression Perpetration Toward Dating Partners: A Brief Report

Abstract: Electronic dating aggression among emerging adults is prevalent and has adverse consequences, yet factors that increase or decrease the risk for perpetrating electronic aggression against a romantic partner are understudied. This investigation advances the literature in two novel ways. First, based on intergenerational transmission of violence theories, we tested the link between family-of-origin aggression (FOA) history and electronic aggression toward romantic partners, using a diverse sample of emerging adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 14 publications
(21 reference statements)
4
19
0
4
Order By: Relevance
“…To our knowledge, little research has analyzed whether predictors and mediators of IPV play a similar role in CDA. Only two studies investigate the link between ACEs and CDA ( Smith-Darden et al, 2016 ; Ramos et al, 2017 ). Both yielded results consistent with those relating to IPV; they showed that physical, sexual, and psychological abuse, family aggression, and family problems (e.g., family member incarceration, family member drug or alcohol use, family member mental illness) were connected with a greater likelihood of perpetrating CDA ( Smith-Darden et al, 2016 ; Ramos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, little research has analyzed whether predictors and mediators of IPV play a similar role in CDA. Only two studies investigate the link between ACEs and CDA ( Smith-Darden et al, 2016 ; Ramos et al, 2017 ). Both yielded results consistent with those relating to IPV; they showed that physical, sexual, and psychological abuse, family aggression, and family problems (e.g., family member incarceration, family member drug or alcohol use, family member mental illness) were connected with a greater likelihood of perpetrating CDA ( Smith-Darden et al, 2016 ; Ramos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies investigate the link between ACEs and CDA ( Smith-Darden et al, 2016 ; Ramos et al, 2017 ). Both yielded results consistent with those relating to IPV; they showed that physical, sexual, and psychological abuse, family aggression, and family problems (e.g., family member incarceration, family member drug or alcohol use, family member mental illness) were connected with a greater likelihood of perpetrating CDA ( Smith-Darden et al, 2016 ; Ramos et al, 2017 ). No study has attempted to document a connection between maladaptive schemas belonging to Disconnection and Rejection and CDA or a possible mediating role of Disconnection and rejection maladaptive schemas in the relationship between ACEs and CDA.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies were also observed regarding the participation of men and women in CDVs. In adults, some studies did not detect gender differences in the frequency of perpetration (Ramos et al, 2017;Reed et al, 2016;Tokunaga, 2011), in the frequency of victimization (Drouin et al, 2015;, or in the chronicity of CDVs (Bennett et al, 2011;Borrajo et al, 2015a;Strawhun et al, 2013;. This was similar in studies with minors (e.g., Muñiz, 2017;Sánchez et al, 2017;Reed et al, 2016;Smith et al, 2018).…”
Section: Research Characteristics and Main Findingsmentioning
confidence: 85%
“…Reported prevalence rates of CDV perpetration in minors ranged from 8.8% (Muñiz, 2017) to 38% (Smith-Darden et al, 2017), and in victimization from 22.3% (Temple et al, 2016) to 41% (Dick et al, 2014). In adults, perpetration figures ranged from 16.3% (Ramos et al, 2017) to 71% (Melander, 2010), and victimization from 20% (Drouin et al, 2015;Strawhun et al, 2013) to 75% (Melander, 2010), 76.5% in women and 77.1% in men (Bennett et al, 2011), considering only global indices, although values above these limits were observed in specific items. As for the frequency of CDV, the mean scores found were generally at the lower end of the scale, in adults (Bennett et al, 2011;Reed et al, 2016), and in minors (Sánchez et al, 2017;Temple et al, 2016), although there were results as disparate as those obtained in the two papers by Borrajo and his team, on the one hand, reporting an average victimization of 23 times in the last six months (Borrajo et al, 2015a), and on the other hand, a much lower average in the last year of the relationship, according to the type of CDV (Borrajo et al, 2015b).…”
Section: Research Characteristics and Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation